How to Engage People with Aphasia in Research: the Before Recommendations - Charalambous, Marina; Kambanaros, Maria (My University, 2024)
Patient and public involvement (PPI) is the active partnership between researchers, patients, and the public in the process of creating and conducting research. The aim of this study was to report the barriers to becoming involved in research as patient partners for people with aphasia (PWA). Semi structured interviews were conducted online with eight people with chronic stroke: four with aphasia and four without. Interviews were subject to thematic analysis. Four key themes were generated for consideration: (1) the types of restrictions that make involvement difficult, (2) the preferred ways of involvement, (3) the support required for meaningful involvement, and (4) the impact of involving “patients” for the research outcomes. Patient groups are willing to be actively involved in research teams if the necessary support for participation is provided. The BEFORE recommendations are available for researchers to consider before initiating coproduced research with stroke and aphasia groups.
Keywords: Patient and Public Involvement; People with Aphasia; Codesign Research